(3OjhGf bGSe GdMeOjs - (3bGSe Hf jMji GdMeOj GdehUdjs
(3ChdgG (B:s
(3CeG HYO(B: (3ajbhd GdYHO GdeaJbQ Edi QMeI QHg GdYdj bGSe Hf jMji GdehUdj(B: (3deG QCjJ GdebUhQI, GdebUhQI Ydi GdeOjM GdfHhj GdoeJSeI HChUGa GdLfGH GdeUWahj s
(3BNQgG (B:s
(3hdjehfI ef hLfI bO JbUUJ HKhH fVGQ cd bdH HgG jMjG QCJ LhOc GdajGV aGUaQ hLggG eNGaI HYO Yf jejfc jG jMji s
(3aj BNQgG CTYGQ HGddZI GdJQcjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B178 s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdOcJhQ eMeO UOjb GdLdjdj HGdehUd (B(1) s
Keywords: (3GdCOHs